Investigating the Effects of Milk on Body Composition: A Comparative Analysis in Diverse Populations - Dorian BARZUCA; Alexandra BARZUCA; Elena-Doina MIRCIOAGA (Romanian Journal of Physical Therapy)
Introduction: Milk consumption is frequently debated for its potential role in weight regulation and modulating body composition. This study aimed to investigate the association between milk intake and body composition parameters among physically untrained students, student athletes, and dialysis patients. Methods and Materials: In a cross-sectional design, 110 participants (78 physically untrained students, 17 student athletes, and 15 dialysis patients) were evaluated for body mass index (BMI), adipose tissue percentage, and muscle tissue percentage. Milk consumption frequency was assessed using a structured questionnaire, and statistical analyses - including the Kruskal-Wallis and Mann-Whitney tests, as well as Pearson correlation - were performed to examine intergroup differences and associations. Results: Significant differences in milk consumption were observed among groups, with dialysis patients reporting the lowest frequency. A positive correlation was identified between milk consumption frequency and muscle tissue percentage (r = 0.266, p < 0.01), while a negative correlation was observed between milk consumption and adipose tissue percentage (r = -0.303, p < 0.01). Discussion: These findings suggest that increased milk intake may contribute to a more favorable body composition, potentially through mechanisms related to lipid metabolism and appetite regulation. Conclusions: Although milk consumption appears to be modestly associated with increased muscle mass and reduced adiposity, further research is warranted to elucidate the underlying physiological mechanisms and to determine the long-term effects of milk intake on body composition.